Restorative Effects of Synbiotics on Colonic Ultrastructure and Oxidative Stress in Dogs with Chronic Enteropathy - Dipak Kumar Sahoo; Tracey Stewart; Emily M. Lindgreen; Bhakti Patel; Ashish Patel; Jigneshkumar N. Trivedi; Valerie Parker; Adam J. Rudinsky; Jenessa A. Winston; Agnes Bourgois-Mochel; Jonathan P. Mochel; Karin Allenspach; et al. (Antioxidants)
Synbiotics can be used to reduce intestinal inflammation and mitigate dysbiosis in dogs with chronic inflammatory enteropathy (CIE). Prior research has not assessed the colonic mucosal ultrastructure of dogs with active CIE treated with synbiotics, nor has it determined a possible association between morphologic injury and signaling pathways. Twenty client-owned dogs diagnosed with CIE were randomized to receive either a hydrolyzed diet (placebo; PL) or a hydrolyzed diet supplemented with synbiotic-IgY (SYN) for 6 weeks. Endoscopic biopsies of the colon were obtained for histopathologic, ultrastructural, and molecular analyses and were compared before and after treatment. Using transmission electron microscopy (TEM), an analysis of the ultrastructural alterations in microvilli length (MVL), mitochondria (MITO), and rough endoplasmic reticulum (ER) was compared between treatment groups. To explore potential signaling pathways that might modulate MITO and ER stress, a transcriptomic analysis was also performed. The degree of mucosal ultrastructural pathology differed among individual dogs before and after treatment. Morphologic alterations in enterocytes, MVL, MITO, and ER were detected without significant differences between PL and SYN dogs prior to treatment. Notable changes in ultrastructural alterations were identified post-treatment, with SYN-treated dogs exhibiting significant improvement in MVL, MITO, and ER injury scores compared to PL-treated dogs. Transcriptomic profiling showed many pathways and key genes to be associated with MITO and ER injury. Multiple signaling pathways and their associated genes with protective effects, including fibroblast growth factor 2 (FGF2), fibroblast growth factor 7 (FGF7), fibroblast growth factor 10 (FGF10), synaptic Ras GTPase activating protein 1 (SynGAP1), RAS guanyl releasing protein 2 (RASGRP2), RAS guanyl releasing protein 3 (RASGRP3), thrombospondin 1 (THBS1), colony stimulating factor 1 (CSF1), colony stimulating factor 3 (CSF3), interleukin 21 receptor (IL21R), collagen type VI alpha 6 chain (COL6A6), ectodysplasin A receptor (EDAR), forkhead box P3 (FoxP3), follistatin (FST), gremlin 1 (GREM1), myocyte enhancer factor 2B (MEF2B), neuregulin 1 (NRG1), collagen type I alpha 1 chain (COL1A1), hepatocyte growth factor (HGF), 5-hydroxytryptamine receptor 7 (HTR7), and platelet derived growth factor receptor beta (PDGFR-β), were upregulated with SYN treatment. Differential gene expression was associated with improved MITO and ER ultrastructural integrity and a reduction in oxidative stress. Conversely, other genes, such as protein kinase cAMP-activated catalytic subunit beta (PRKACB), phospholipase A2 group XIIB (PLA2G12B), calmodulin 1 (CALM1), calmodulin 2 (CALM2), and interleukin-18 (IL18), which have harmful effects, were downregulated following SYN treatment. In dogs treated with PL, genes including PRKACB and CALM2 were upregulated, while other genes, such as FGF2, FGF10, SynGAP1, RASGRP2, RASGRP3, and IL21R, were downregulated. Dogs with CIE have colonic ultrastructural pathology at diagnosis, which improves following synbiotic treatment. Ultrastructural improvement is associated with an upregulation of protective genes and a downregulation of harmful genes that mediate their effects through multiple signaling pathways.